Decentralized solar-powered drinking water ozonation in Western Kenya: an evaluation of disinfection efficacy [version 2; peer review: 2 approved, 1 approved with reservations] - Colin Hendrickson (Gates Open Research, 2020)
Background: Decentralized drinking water treatment methods generally apply membrane-based treatment approaches. Ozonation of drinking water, which previously has only been possible at large centralized facilities, can now be accomplished on a small-scale using microplasma technology. The efficacy of decentralized solar-powered drinking water treatment systems has not previously been described. Methods: We established a 1,000L decentralized solar-powered water treatment system located in Kisumu County, Kenya. Highly contaminated surface water is pumped to the treatment system, which includes flocculation and filtration steps prior to ozonation. Turbidity, total coliform bacteria, and E. coli were measured at various stages of water treatment, and bacterial log reduction values (LRVs) were calculated. Results: Forty-seven trials were conducted in which1000L of water were flocculated, filtered, and ozonated for 180 minutes. Baseline turbidity and E. coli concentrations were reduced from a median of 238 nephelometric turbidity units (NTU) and 2,419.7 most probable number/100mL, respectively, in surface water to 1.0 NTU and undetectable E. coli after ozonation for 180 minutes. The median E. coli LRV was 3.99. Conclusions: The solar-powered, decentralized water treatment system that utilizes ozonation for disinfection was founded to reduce E. coli by more than 3 log-orders of magnitude despite the high turbidity of the raw water. Further research is needed to characterize limitations, scalability, economic viability, and community perspectives that could help determine the role for similar systems in other settings.